The cost of future policy - Koshima, Yugo,Harris, Jason,Tieman, Alexander F.,Sanctis, Alessandro de (International Monetary Fund, 2021)
This paper compiles the Intertemporal Public Sector Balance Sheets for all G7 countries and examines their relationship with government borrowing costs. In 2018, all G7 countries have negative Intertemporal Net Financial Worth (INFW), falling short of their intertemporal budget constraint. A decomposition of the evolution of INFW shows that short-term fluctuations are mainly driven by fiscal policy changes, while in the long run demographic changes and health and pension obligations play a larger role. We find that on average a 10 percentage point of GDP increase in INFW reduces the (future) 10-1 year sovereign yield curve spread by 2.8 basis points. This results suggest that financial markets pay attention to governments' future policy obligations, in addition to its current assets and liabilities
10.5089/9781513573335.001
Keywords: Graue Literatur; Public Sector Balance Sheet; G7; Canada; France; Germany; Italy; UK; US; Fiscal Sustainability; Intertemporal Net Financial Worth; Japan; Fiscal Policy; Foreign Exchange; Informal Economy; Public Administration; Underground Econom; Public Finance; International Economics; Economics: General; Accounting; Public Sector Accounting and Audits; National Government Expenditures and Health; Social Security and Public Pensions; Economic & financial crises & disasters; Economics of specific sectors; Financial reporting; financial statements; Public finance & taxation; Financial statements; Public financial management (PFM); Health care spending; Expenditure; Fiscal stance; Pension spending; Currency crises; Informal sector; Economics; Fiscal policy; Finance; Public; Accounting; Expenditures; Public; Pensions; Macroeconomics